PENGARUH E-WORM DAN PERSEPSI RESIKO TERHADAP MINAT BELI KONSUMEN PADA KONSUMEN CITRA DIMSUM MEDAN - Harahap, Ilham Soleh; Royani, Ida (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This case study is to determine and analyze the influence of worms and risk perception on consumer purchasing interest in Citra Dimsum Medan. The research method used is exploratory research, where variables are measured using a Likert scale. Data collection methods are carried out by interview, with a questionnaire and documentation study. The population in this study were all consumers at the Shifa Medan Cosmetics Counter. totaling 54 people. Sampling using the saturated sampling method or better known as the census. In this study, the population was relatively small, namely 54 people. Data processing used SPSS version 24 software, with descriptive analysis and multiple regression analysis hypothesis testing. The results of the study indicate that: (1) partially the e-worm variable affects consumer purchasing interest in Citra Dimsum Medan...; (2) partially the risk perception variable affects consumer purchasing interest in Citra Dimsum Medan.; (3) simultaneously there is a positive and significant influence between the e-worm variable and risk perception on consumer purchasing interest in Citra Dimsum Medan.